Silicon negative electrode material and preparation method and application thereof
By constructing a modified cladding layer of cyclized polyacrylonitrile and fast ion conductors on the surface of the silicon-based anode material, the problems of low conductivity and volume expansion of the silicon-based anode material are solved, and the cycle stability and rate performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202510123444.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-28
AI Technical Summary
Silicon-based anode material has problems such as low electron/ion conductivity, large volume expansion after lithiation, and poor interface compatibility with sulfide solid electrolytes in lithium-ion batteries, resulting in limited capacity performance, low first efficiency and short cycle life.
The modified cladding layer is constructed using cyclized polyacrylonitrile and fast ion conductors. By buffering volume expansion, inhibiting interface side reactions and improving lithium ion diffusion, the conductivity and interface compatibility of silicon negative electrode materials are improved.
It significantly improves the cycle stability and rate performance of silicon materials, improves interface compatibility with sulfide solid electrolytes, and extends the cycle life of the battery.
Smart Images

Figure CN119725502A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon negative electrode material and a preparation method and application thereof. Background Art
[0002] Since its introduction, lithium-ion batteries (LIBs) have been widely used in 3C electronics, electric vehicles, and grid energy storage. However, due to the flammability of liquid electrolytes and the limited theoretical specific capacity of graphite anodes (372 mAh g -1 ), existing commercial liquid lithium-ion batteries are difficult to meet the market's growing demand for battery energy density and safety. In recent years, solid-state batteries based on solid electrolytes (oxides, sulfides and polymer solid electrolytes, etc.) have received widespread attention from academia and industry due to their excellent safety. At the same time, solid electrolytes are more compatible with high-energy-density negative electrode materials (such as lithium metal, silicon-based materials), which helps to break through the bottleneck of commercial lithium-ion battery energy density. Among the current technical routes for battery solidification, sulfide solid electrolytes have the highest lithium ion conductivity, extremely low electronic conductivity, and excellent mechanical properties and mechanical ductility, and are one of the most promising material systems for realizing all-solid-state batteries.
[0003] Compared with lithium metal, silicon-based materials have significant advantages in raw material cost, interface stability, processability, and compounding with existing graphite materials. In addition, the lithiation potential of silicon materials is about 0.4V vs. Li + / Li, which helps to alleviate the interface reaction between the negative electrode and the sulfide solid electrolyte and avoid the problem of lithium dendrite growth. However, silicon-based negative electrode materials still face many challenges in the process of practical development. The capacity of silicon-based negative electrodes is limited, the first efficiency is low, and the cycle life is short. The root cause lies in the low electronic conductivity and lithium ion diffusion coefficient of silicon materials, large volume fluctuations during the cycle, low cycle reversibility, and poor interface stability.
[0004] At the electrode level, due to the low electronic conductivity and lithium ion diffusion coefficient of silicon negative electrode, it is necessary to mix and compound conductive agent and solid electrolyte powder when preparing composite electrode, and use external pressure to compact the solid-solid contact between powder particles to reduce electrode polarization. At the material level, on the one hand, nano silicon, porous silicon, silicon nanowires, etc. are used as active materials, and on the other hand, by introducing polymer, amorphous carbon or transition metal coating on the surface of silicon material, the solid-solid contact between active material and solid electrolyte is improved, the electron / ion transfer is improved, the interface resistance is reduced, and the silicon material is prevented from cracking and pulverizing.
[0005] In order to improve the solid-solid contact and interface stability between silicon and sulfide solid electrolyte, patent CN118712336A discloses a method for preparing a silicon negative electrode material coated with trifluoromethylboric acid, which helps to build a good SEI buffer layer between silicon and solid electrolyte. Patent CN117936725A discloses a silicon negative electrode coated with a fast ion conductor and silicon oxide and applied to all-solid-state batteries. The presence of fast ion conductor improves the lithium ion diffusion of silicon negative electrode materials, and the silicon oxide coating layer buffers the volume expansion of silicon particles to a certain extent.
[0006] However, the single-function coating layer on the surface of silicon material cannot achieve a balance between elasticity, electronic / ionic conductivity and binding force, and it is difficult to solve the problems of low conductivity and volume expansion of silicon negative electrode at the same time. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a silicon negative electrode material that can simultaneously solve the problems of low electronic / ionic conductivity of the silicon negative electrode, large volume expansion after lithiation, and poor interface compatibility with sulfide solid electrolytes; another purpose of the present invention is to provide a method for preparing the silicon negative electrode material; another purpose of the present invention is to provide an application of the silicon negative electrode material.
[0008] The present application discloses a silicon negative electrode material, comprising a silicon material substrate and a coating layer coated on the surface of the silicon material substrate; the coating layer comprises cyclized polyacrylonitrile and a fast ion conductor.
[0009] The all-silicon negative electrode in the solid-state battery system requires silicon, solid electrolyte and conductive agent to be mechanically mixed before being made into sheets. Therefore, the solid-solid contact between the active material and the solid electrolyte particles in the electrode is poor, resulting in limited local lithium ion and electron conduction and increased electrode polarization. In addition, the carbon layer on the surface of the silicon-carbon material has many defects, and direct contact with the sulfide solid electrolyte will be accompanied by serious interfacial side reactions, causing active lithium loss and SEI layer thickening, resulting in reduced initial efficiency and capacity of the silicon material. The single-function coating on the surface of the silicon material cannot achieve a balance between elasticity, electronic / ionic conductivity and binding force, and it is difficult to simultaneously solve the problems of low conductivity and volume expansion of the silicon negative electrode.
[0010] Oxide solid electrolytes and polymer solid electrolytes have good compatibility with silicon materials, but sulfide solid electrolytes will have more interfacial side reactions when they are in direct contact with silicon or the outer carbon shell.
[0011] Cyclized polyacrylonitrile buffers volume expansion and inhibits interface side reactions; fast ion conductors improve interface contact and increase the lithium ion diffusion coefficient. The present invention constructs a modified coating layer that takes into account elasticity, conductivity and chemical stability, and is intended to simultaneously solve the problems of low electron / ion conductivity of silicon negative electrode, large volume expansion after lithiation, and poor interface compatibility with sulfide solid electrolyte.
[0012] Furthermore, the silicon material matrix includes any one of silicon carbon, silicon oxygen, nano silicon or porous silicon, and the D50 of the silicon material matrix particles is 3-10 μm.
[0013] Furthermore, the thickness of the coating layer is 20-200 nm; the coating amount of the cyclized polyacrylonitrile accounts for 1-20% of the total mass of the silicon negative electrode material.
[0014] Furthermore, the fast ion conductor includes one or more of LLZO, LLTO, LATP, Li3GdCl3Br3, and Li2ZrCl6.
[0015] The present invention also discloses a method for preparing a silicon negative electrode material, comprising the following steps:
[0016] S1: dispersing a silicon material matrix and polyacrylonitrile in an organic solvent, and after the polyacrylonitrile is dissolved in the organic solvent, adding a fast ion conductor and mixing evenly to form a mixed slurry;
[0017] S2: Dry the mixed slurry, remove the organic solvent, crush it, and perform heat treatment in a protective gas atmosphere to obtain the silicon negative electrode material as described above.
[0018] like Figure 1 As shown, the present invention uses silicon material as a matrix, adopts a liquid phase coating method and constructs a polyacrylonitrile-based coating layer on the surface of the material. Subsequently, the heat treatment process is controlled to convert polyacrylonitrile into cyclized polyacrylonitrile, and a modified coating layer with balanced flexibility, conductivity and lithium ion diffusion coefficient is obtained. Due to the higher demand for ion transfer capacity in solid-state battery systems, fast ion conductors are introduced into the coating layer to further improve lithium ion transfer. The construction of a functionalized co-coating layer simultaneously solves the problems of low conductivity and volume expansion of silicon negative electrode materials. In addition, the presence of a highly chemically stable coating layer avoids direct contact between silicon-carbon materials and sulfide solid electrolytes, preventing interfacial side reactions. Thanks to the good electronic / ionic conductivity of the modified coating layer, the volume expansion of the buffered silicon negative electrode, and the avoidance of interfacial side reactions, the cycle stability and rate performance of the silicon material are significantly improved.
[0019] Furthermore, in the step S1, the ratio of the added mass of the polyacrylonitrile to the added mass of the fast ion conductor is 1:(0.1-0.5).
[0020] Furthermore, in step S2, the drying temperature is 80-150°C.
[0021] Furthermore, in step S2, the heat treatment temperature is 250-400° C., and the treatment time is 0.5-2 h.
[0022] By controlling the heat treatment temperature, in a protective gas atmosphere, polyacrylonitrile undergoes a reaction as shown in formula (1) to form cyclized polyacrylonitrile, which has the advantages of high chemical stability and high electrical conductivity.
[0023] (1).
[0024] Furthermore, in step S1, the organic solvent includes one or more of N,N-dimethylformamide (DFM), dimethyl sulfoxide (DMSO), and N,N-dimethylacetamide (DMAc).
[0025] The present invention also provides an application of a silicon negative electrode material, such as the silicon negative electrode material described above is applied to the preparation of a lithium ion battery.
[0026] The present invention provides a silicon negative electrode material, in which a uniform cyclized polyacrylonitrile and fast ion conductor coating layer is constructed on the surface of a silicon material substrate. The good electronic conductivity and elasticity of the cyclized polyacrylonitrile and the excellent ionic conductivity of the fast ion conductor are helpful to buffer the volume expansion of the silicon-carbon material, accelerate the lithium ion transmission kinetics, and effectively improve the rate performance of the negative electrode material. The cyclized polyacrylonitrile has high chemical stability and strong compatibility with silicon materials and sulfide solid electrolytes. As a buffer layer between the silicon material and the sulfide solid electrolyte, the cyclized polyacrylonitrile avoids direct contact between the silicon-carbon material and the sulfide solid electrolyte, inhibits interface side reactions, and effectively improves the battery cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic structural diagram of the silicon negative electrode material of the present invention. DETAILED DESCRIPTION
[0028] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] Example 1
[0030] S1: Take 200 g of vapor-deposited silicon-carbon material (D50 = 5 μm) and 5 g of (polyacrylonitrile) PAN and disperse them in 1 L of (dimethylformamide) DMF. Heat to 80 °C with continuous stirring. After PAN is completely dissolved, add 2 g of nano-LLZO and fully disperse them to form a mixed slurry.
[0031] S2: Raise the temperature of the mixed slurry to 100°C, continue stirring until the organic solvent is completely evaporated, and crush to obtain a precursor powder; place the obtained precursor powder in a box furnace, use argon as a protective atmosphere, heat to 320°C at a heating rate of 5°C / min, and keep the temperature constant for 1h for low-temperature heat treatment to obtain a silicon negative electrode material.
[0032] Example 2
[0033] S1: Take 200 g of vapor-deposited silicon-carbon material (D50 = 5 μm) and 5 g of PAN and disperse them in 1 L of DMF. Heat to 80 °C while stirring continuously. After PAN is completely dissolved, add 1 g of nano-LLTO and fully disperse to form a mixed slurry.
[0034] S2: Raise the temperature of the mixed slurry to 100°C, continue stirring until the organic solvent is completely evaporated, and crush to obtain a precursor powder; place the obtained precursor powder in a box furnace, use argon as a protective atmosphere, heat to 300°C at a heating rate of 5°C / min, and keep the temperature constant for 2h for low-temperature heat treatment to obtain a silicon negative electrode material.
[0035] Example 3
[0036] S1: Take 200 g of vapor-deposited silicon-carbon material (D50 = 5 μm) and 4 g of PAN and disperse them in 1 L of DMF. Heat to 60 °C while stirring continuously. After PAN is completely dissolved, add 2 g of Li2ZrCl6 and fully disperse to form a mixed slurry.
[0037] S2: Raise the temperature of the mixed slurry to 100°C, continue stirring until the organic solvent is completely evaporated, and crush to obtain a precursor powder; place the obtained precursor powder in a box furnace, use argon as a protective atmosphere, heat to 380°C at a heating rate of 5°C / min, and keep the temperature constant for 1h for low-temperature heat treatment to obtain a silicon negative electrode material.
[0038] Comparative Example 1
[0039] Take 200 g of vapor-deposited silicon carbon (D50 = 5μm) and 5 g of LLZO and disperse them in 1 L of DMF. Heat to 80°C while stirring continuously. After being fully dispersed, raise the solution temperature to 100°C and continue stirring until the solvent is completely evaporated to obtain a silicon negative electrode material coated with a fast ion conductor.
[0040] Comparative Example 2
[0041] Take 200 g of gas-phase silicon carbon material (D50 = 5μm) and 5 g of PAN and disperse them in 1 L of DMF. Heat to 80°C while stirring continuously. After PAN is completely dissolved, raise the temperature of the mixed solution to 100°C, continue stirring until the organic solvent is completely evaporated, and crush to obtain powder.
[0042] The obtained powder was placed in a box furnace, heated to 380°C at a heating rate of 5°C / min with argon as the protective atmosphere, and kept at a constant temperature for 1 hour for low-temperature heat treatment to obtain a silicon negative electrode material.
[0043] Performance Test:
[0044] The silicon negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were assembled into solid-state half-cells and electrochemical performance tests were performed. The specific scheme is as follows:
[0045] Solid-state half-cell assembly and electrochemical testing: 100 mg of Li6PS5Cl solid electrolyte powder was pre-pressed at 1 t, and then 2 mg of silicon negative electrode material and 1 mg of Li6PS5Cl solid electrolyte powder were evenly dispersed on one side, and the pressure was maintained at 7 t for 3 min, and then on the other side, In foil and Li foil were attached in sequence, and then the pressure was maintained at 3 t for about 1 min, and then the screws of the battery mold were tightened to obtain a solid-state half-cell. All batteries were tested at room temperature, and the cycle test rate was 0.1 C. The test results are shown in Table 1.
[0046] Table 1 Test results of solid half-cells assembled in Examples 1-3 and Comparative Examples 1-2
[0047] Material First lithium removal capacity (0.1C; mAh / g) 50-lap retention rate (%) Lithium removal capacity (2C; mAh / g) Example 1 1965 84.3 1453 Example 2 2037 88.7 1619 Example 3 1608 81.1 1101 Comparative Example 1 1470 66.3 733 Comparative Example 2 1332 56.1 608
[0048] As shown in Table 1, the first lithium removal capacity, 50-cycle retention rate, and lithium removal capacity of Examples 1-3 are all higher than those of Comparative Examples 1-2. This shows that the cyclized polyacrylonitrile and coating layer on the surface of the silicon-carbon material of the silicon negative electrode material prepared in Examples 1-3 help to buffer the volume expansion of nano-silicon lithium insertion, while avoiding the interfacial side reactions caused by direct contact between the sulfide solid electrolyte and the silicon material. After the composite nano-fast ion conductor is used, the solid-solid contact between the negative electrode particles is further improved, and the interfacial lithium ion diffusion resistance is reduced, thereby significantly improving the first-cycle lithium removal capacity and coulomb efficiency of the silicon-carbon composite material, and improving the cycle stability of the material.
[0049] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A silicon negative electrode material, characterized in that: The invention comprises a silicon material substrate and a coating layer coated on the surface of the silicon material substrate; the coating layer comprises cyclized polyacrylonitrile and a fast ion conductor.
2. A silicon negative electrode material according to claim 1, characterized in that: The silicon material matrix includes any one of silicon carbon, silicon oxygen, nano silicon or porous silicon, and the D50 of the silicon material matrix particles is 3-10 μm.
3. A silicon negative electrode material according to claim 2, characterized in that: The thickness of the coating layer is 20-200 nm; the coating amount of the cyclized polyacrylonitrile accounts for 1-20% of the total mass of the silicon negative electrode material.
4. A silicon negative electrode material according to claim 3, characterized in that: The fast ion conductor includes one or more of LLZO, LLTO, LATP, Li3GdCl3Br3, and Li2ZrCl6.
5. A method for preparing a silicon negative electrode material, characterized in that: The following steps are involved: S1: dispersing a silicon material matrix and polyacrylonitrile in an organic solvent, and after the polyacrylonitrile is dissolved in the organic solvent, adding a fast ion conductor and mixing evenly to form a mixed slurry; S2: Drying the mixed slurry, removing the organic solvent, crushing, and heat treating in a protective gas atmosphere to obtain the silicon negative electrode material as described in any one of claims 1 to 4.
6. The method for preparing a silicon negative electrode material according to claim 5, characterized in that: In the step S1, the ratio of the added mass of the polyacrylonitrile to the added mass of the fast ion conductor is 1:0.1-0.
5.
7. The method for preparing a silicon negative electrode material according to claim 5, characterized in that: In the step S2, the drying temperature is 80-150°C.
8. The method for preparing a silicon negative electrode material according to claim 5, characterized in that: In step S2, the heat treatment temperature is 250-400° C. and the treatment time is 0.5-2 h.
9. The method for preparing a silicon negative electrode material according to claim 5, characterized in that: In the step S1, the organic solvent includes one or more of N,N-dimethylformamide, dimethyl sulfoxide, and N,N-dimethylacetamide.
10. An application of a silicon negative electrode material, characterized in that: The silicon negative electrode material as described in claims 1 to 4 is used in the preparation of lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of improved room temperature electron ion fast transfer electrode slice for solid-state secondary lithium battery
CN105932225A
Silicon-carbon composite negative electrode for solid-state batteries and preparation method of silicon-carbon composite negative electrode
CN108232156A
Fast ion lithium salt coated-type silicon carbide material and preparation method thereof
CN108493428A
High-conductivity silicon-oxygen negative electrode material and application thereof
CN111048756A
Silicon negative electrode active material and preparation method thereof, negative electrode plate and solid-state battery
CN117936725A
Cited By
Composite coating material as well as preparation method and application thereof
CN120389031A
A composite coating material and its preparation method and application
CN120389031B
Surface modified hard carbon material as well as preparation method and application thereof
CN121097037A
Surface-modified hard carbon material and preparation method and application thereof
CN121097037B
Silicon-based composite negative electrode material and preparation method and application thereof
CN121366881A